1994
DOI: 10.1002/bjs.1800811044
|View full text |Cite
|
Sign up to set email alerts
|

Herniography for occult hernia and groin pain

Abstract: In a prospective 3-year study herniography was used to assess patients with unexplained groin pain in whom clinical signs were inconclusive. Fifty-two patients were studied. No serious complications were observed. Twenty-two hernias were identified in 18 patients. The positive herniographic findings were confirmed at operation in 12 patients. Of 34 patients with a negative herniogram, none has developed a hernia. Pain settled spontaneously in 29 patients and five were referred to a pain clinic for further mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…This is a more quantitative and perhaps objective feature in the evaluation for hernias, and has been noted by others who have used groin ultrasound. Chou et al [3] described the use of groin ultrasound in children and determined that an internal ring larger than 4 mm or an increase of 2 mm or more with the Valsalva maneuver were strong indicators of a patent processus vaginalis or hernia. We did not routinely document the size of the internal ring or quantitate the change in size, but feel that in the future, a similar criteria could be developed for the evaluation of adult hernias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a more quantitative and perhaps objective feature in the evaluation for hernias, and has been noted by others who have used groin ultrasound. Chou et al [3] described the use of groin ultrasound in children and determined that an internal ring larger than 4 mm or an increase of 2 mm or more with the Valsalva maneuver were strong indicators of a patent processus vaginalis or hernia. We did not routinely document the size of the internal ring or quantitate the change in size, but feel that in the future, a similar criteria could be developed for the evaluation of adult hernias.…”
Section: Discussionmentioning
confidence: 99%
“…Herniography has been used for many years with variable results, although it is invasive and thus not without possible complications, [3,4]. Also, herniography will not detect lipomas of the cord that have no peritoneal protrusion.…”
Section: Discussionmentioning
confidence: 99%
“…35 More commonly, herniography is diagnostic 12% to 36% of the time. 7,8,14,18,22,40 This is not to say herniography is not beneficial. It is, as demonstrated by a high true-positive rate (96%), seen in patients who subsequently went on to surgery.…”
Section: Number 455 February 2007mentioning
confidence: 99%
“…In surgery and urology clinics, herniography is usually used to illuminate the etiology of pain of unknown cause in the pelvic area and to diagnose uncertain or occult hernias in the preoperative period [1][2][3]. Herniography was first descirbed in Canada in 1967 [1].…”
Section: Discussionmentioning
confidence: 99%
“…Herniography was first descirbed in Canada in 1967 [1]. Ekberg et al reported that the herniography was a highly sensitive and safe method of diagnosis.…”
Section: Discussionmentioning
confidence: 99%